Determinants of Primary School Choice in Malaysia: School Proximity and Ethnicity-Related Reasons - Ting, Su Hie; Lee, D.P.-Y. (Routledge, 2019)
The study examined determinants of primary school choice among parents in Malaysia, and the decision maker and social influences in the school choice. It draws on qualitative data from semi-structured interviews with 43 middle-class parents from three ethnic groups (Chinese, Malay, and Indigenous). Results showed that school proximity and ethnicity-related reasons are leading factors influencing parental school choice. Medium of instruction, school academic reputation, and feeder to a preferred secondary school appear to be separate reasons but act as a proxy to ethnicity as the primary factor determining the choice of Chinese- or Malay-medium primary school by parents. The results also showed that mothers are more likely to make school choice decisions than fathers, but the reasons for school choice are similar. The primary social influences on their school choice come from friends and education personnel in preschools and schools. The Indigenous parents tend to be more subject to social pressure in making school choices than the Chinese and Malay parents, who mostly enroll their children in Chinese- and Malay-medium primary schools, respectively. However, these findings on school choice and ethnic segregation are limited to this sample and constrained by the socio-political context of the education system.